$(a)$ 从 $3x-y+11$ 和 $-y-11$ 的和中减去 $3x-y-11$。
$(b)$ 从 $4+3x$ 和 $5-4x+2x^2$ 的和中减去 $3x^2-5x$ 和 $-x^2+2x+5$ 的和。
题目:$(a)$ 从 $3x-y+11$ 和 $-y-11$ 的和中减去 $3x-y-11$。
$(b)$ 从 $4+3x$ 和 $5-4x+2x^2$ 的和中减去 $3x^2-5x$ 和 $-x^2+2x+5$ 的和。
解答
a). $3x-y+11$ 和 $-y-11$ 的和为:
$=(3x-y+11)+(-y-11)$
$=3x-y+11-y-11$
$=3x-2y$
现在,我们从 $3x-2y$ 中减去 $3x-y-11$
$(3x-2y)-(3x-y-11)$
$=3x-2y-3x+y+11$
$=-y+11$
b). $4+3x$ 和 $5-4x+2x^2$ 的和为:
$=(4+3x)+(5-4x+2x^2)$
$=4+3x+5-4x+2x^2$
$=2x^2-x+9$
$3x^2-5x$ 和 $-x^2+2x+5$ 的和为:
$=(3x^2-5x)+(-x^2+2x+5)$
$=3x^2-5x-x^2+2x+5$
$=2x^2-3x+5$
现在,我们从 $2x^2-x+9$ 中减去 $2x^2-3x+5$
$=(2x^2-x+9)-(2x^2-3x+5)$
$=2x+4$
广告